Teaching Writing in Social Work: an Online Literature Review (2000-2022) - Bórtoli, Pamela Virginia; Carlino, Paula (Cuadernos de Trabajo Social, 2023)
This study used Boolean searches to identify the main research concerning the teaching of writing in social work by surveying publications on Google Scholar. We used key terms to collect 11 publications in Spanish and 16 in English, producing an overall corpus of 27 texts. The texts showed certain trends in the teaching of writing in social work between 2000 and 2022. In the English language, there appears to be a consolidated body of research examining writing in social work and a rising interest in how it is taught. In contrast, publications in Spanish are scarce and consider writing but do not address the way it is taught. This lack of publications in Spanish is notable considering the centrality of writing to professional activity and interventions and academic participation in the field of social work.